Combination of Soy Protein, Amylopectin, and Chromium Stimulates Muscle Protein Synthesis by Regulation of Ubiquitin-Proteasome Proteolysis Pathway after Exercise - Kayri, Veysi; Orhan, Cemal; Tuzcu, Mehmet; Defo, Patrick Brice Deeh; Telceken, Hafize; Irmak, Mehmet; Şahin, Kazım (Springernature, 2019)
The present study was undertaken to investigate the effect of the combination of soy protein, amylopectin, and chromium (SAC) on muscle protein synthesis and signal transduction pathways involved in protein synthesis (mTOR pathways, IGF-1, and Akt(Ser473)) and proteolysis (FOXO1(Ser256); MURF1, MAFbx) after exercise. Thirty-five Wistar rats were randomly divided into five groups: (1) control (C); (2) exercise (E); (3) exercise + soy protein (3.1 g/kg/day) (E + S); (4) exercise + soy protein + chromium (E + S + Cr); (5) exercise + soy protein + amylopectin + chromium (E + S + A + Cr). Post-exercise ingestion of SAC significantly increased the fractional rate of protein synthesis (FSR), insulin, glycogen, and amino acid levels with the highest effect observed in E + S + A + Cr group (P < 0.05). However, SAC supplementation decreased the lactic acid concentration (P < 0.05). A reduction in forkhead box protein O1 (FOXO1) and forkhead box protein O3 (FOXO3) (regulators of ubiquitin-related proteolysis) and muscle atrophy F-box (MAFbx) levels was noted after treatment with SAC (P < 0.05). Insulin-like growth factor 1(IGF-1) level was increased in the E + S, E + S + Cr, and E + S + A + Cr groups (P < 0.05). While the phosphorylation of 4E-BP1(Thr37/46), Akt(Ser473), mTOR(Ser2448), and S6K1(Thr389) levels increased after SAC supplementation, phosphorylated muscle ring finger 1 (MuRF-1, an E3-ubiquitin ligase gene) was found to be significantly lower compared with the E group (P < 0.05). These results indicate that SAC supplementation improves FSR, insulin, and glycogen levels after exercise. SAC improves protein synthesis by inhibiting the ubiquitin-proteasome pathway and inducing anabolic metabolism.
Keywords: Soy protein; Amylopectin; Chromium; Protein synthesis; Ubiquitin-proteasome pathway